Usability Evaluation of SIMAK at Udayana University Using Outlier Identification with Webuse and Heuristic Methods - Deppy librata; Wulaning Ayu, Putu Desiana; Huizen , Roy Rudolf (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Universities require reliable and user-friendly academic information systems to support teaching, learning, and administrative processes. However, the usability of such systems often encounters obstacles that affect user satisfaction and operational efficiency. This study evaluates the usability of the Sistem Informasi Manajemen Akademik (SIMAK) at Udayana University using a combined Webuse questionnaire and Heuristic Evaluation approach. A total of 100 student responses were collected, and outlier identification using standard deviation analysis removed 34 inconsistent responses. This step was essential for preventing inflated Webuse scores and ensuring that the final dataset (n = 66) more accurately reflected typical user experiences.The Webuse results classify all usability dimensions in the “Excellent” category Content Organization & Readability (0.86), Navigation & Links (0.83), User Interface Design (0.84), and Performance & Effectiveness (0.81). However, the heuristic evaluation conducted by four expert evaluators identified 19 moderate to high-severity issues, revealing critical weaknesses in system responsiveness, interface consistency, and error prevention. These contrasting outcomes highlight that high perceived satisfaction does not necessarily align with expert-validated usability standards.The main contribution of this study lies in integrating outlier detection to refine questionnaire-based usability data, resulting in more valid interpretations. The findings offer practical recommendations for improving SIMAK’s performance, interface clarity, and error-handling mechanisms, while providing methodological insights for future usability evaluations.